MODERN PROBLEMS OF LEGAL EVALUATION AND INDIVIDUALIZATION OF LIABILITY FOR CRIMES INVOLVING ARTIFICIAL INTELLIGENCE-BASED UNMANNED VEHICLES - Normanov Okhunjon Eshnazar ugli (PT. Antis International Publisher, 2026)
Objective: This scientific article comprehensively analyzes the most pressing problems of the criminal-legal evaluation of traffic accidents involving unmanned vehicles equipped with artificial intelligence technologies in modern society. Method: Within the framework of the research, gaps in the current criminal legislation have been thoroughly studied, particularly theoretical and practical issues such as identifying the subject of the crime, distinguishing between negligence and intentional guilt, and establishing the boundaries of legal liability for the manufacturer, programmer, remote operator, and vehicle owner. By engaging in a scientific debate with the views of foreign scholars and advanced international practices, the author has developed his own personal approaches. Results: The article also deeply discusses the ethical dilemmas of robotics, the criminal consequences of cyberattacks on computer systems, and the necessity of introducing corporate criminal liability. Novelty: At the end of the study, detailed, scientifically grounded, and step-by-step proposals and recommendations are put forward aimed at adapting the Criminal Code of the Republic of Uzbekistan to modern technological challenges, creating special blanket norms, and developing clear legal mechanisms for investigating such crimes.